2012
DOI: 10.1038/ki.2012.226
|View full text |Cite
|
Sign up to set email alerts
|

Signaling through the interleukin-18 receptor α attenuates inflammation in cisplatin-induced acute kidney injury

Abstract: Interleukin (IL)-18 is produced by leukocytes and renal parenchymal cells (tubular epithelial cells, podocytes, and mesangial cells). The IL-18 receptor (IL-18R) is expressed on these cells in cisplatin-induced acute kidney injury, but the role of IL-18R is unknown. To help define this, we compared IL-18Rα knockout with wild-type mice in cisplatin-induced acute kidney injury and found deteriorated kidney function, tubular damage, increased accumulation of leukocytes (CD4(+) and CD8(+) T-cells, macrophages, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 30 publications
1
48
1
Order By: Relevance
“…Inflammation is an important factor in pathogenesis of the cisplatin-induced renal injury (Faubel et al, 2007;Nozaki et al, 2012). Another plausible mechanism of CDDP toxicity may be the generation of reactive oxygen species (ROS), such as hydrogen peroxide (H 2 O 2 ), which may interact with DNA, lipids, and proteins (Sun, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation is an important factor in pathogenesis of the cisplatin-induced renal injury (Faubel et al, 2007;Nozaki et al, 2012). Another plausible mechanism of CDDP toxicity may be the generation of reactive oxygen species (ROS), such as hydrogen peroxide (H 2 O 2 ), which may interact with DNA, lipids, and proteins (Sun, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Blocking the IL-36Ra or the IL-IR pathway mimicked the effects of IL-38 on the production of Th17 cytokines (98)(99)(100)(101)(102). It has been observed that IL-38 shares primary amino acid homology with ILIRa and IL-36Ra but is inconsistent with binding to the IL-18R (103)(104)(105)(106). Some effects ofIL-38 and IL-36RA remain unclear, for instance, why they decrease pro-inflammatory cytokines in peripheral blood mononuclear cells whereas increased proinflammatory cytokines in dendritic cells.…”
Section: Il-38 (Il-lflo)mentioning
confidence: 99%
“…36 IL-18 is clearly expressed by tubular epithelial cells in addition to infiltrating immune cells, 37 but if the tubular expression of IL-18 is inflammasomedependent or not and its contribution to kidney injury remains under debate. 38,39 The strong induction of IL-18 inside the kidney upon injury has raised much attention as IL-18 could be a useful urinary biomarker of kidney injury as discussed in detail elsewhere. 40 Inflammasome activation by intracellular bacteria or LPS can induce necrotic cell death, referred to as pyroptosis.…”
Section: Il-1 Receptormentioning
confidence: 99%